2022
DOI: 10.3390/antibiotics11081041
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Phenotypic Characterization of Cutibacterium acnes Bacteriophages Isolated from Acne Patients

Abstract: Cutibacterium acnes is a pathogen that can cause acne vulgaris, sarcoidosis, endodontic lesions, eye infections, prosthetic joint infections, and prostate cancer. Recently, bacteriophage (phage) therapy has been developed as an alternative to antibiotics. In this study, we attempted to isolate 15 phages specific to C. acnes from 64 clinical samples obtained from patients with acne vulgaris. Furthermore, we sequenced the genomes of these three phages. Bioinformatic analysis revealed that the capsid and tape mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…2 , Table 3 , Supplemental Fig. S 2 , and Table S3 ) and agreed with other worldwide reports, with a rate of approximately 88% antibiotic sensitivity among clinical isolates 21 , 22 , 33 36 . Furthermore, although we noted a significant correlation in our C. acnes collection between the A1 SLST type and the antibiotic resistance strains, no correlation was detected between any SLST type and phage-resistance strains (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2 , Table 3 , Supplemental Fig. S 2 , and Table S3 ) and agreed with other worldwide reports, with a rate of approximately 88% antibiotic sensitivity among clinical isolates 21 , 22 , 33 36 . Furthermore, although we noted a significant correlation in our C. acnes collection between the A1 SLST type and the antibiotic resistance strains, no correlation was detected between any SLST type and phage-resistance strains (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 90%
“…One protein that did not follow this distribution was QPB11808.01 (as in PAVL33). This CDS was annotated as tape measure protein 22 , present in PAVL20, PAVL33, PAVL34, PAVL45, and on the other four phages (Fig. 1b and Supplemental Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all studied cell-free supernatant-medicinal oil combinations showed marked synergistic activity against S. aureus, E. coli, and Klebsiella pneumoniae. In another study, Kim et al (2022) reported the synergistic antibacterial potential of lactic acid bacteria combined with Curcuma longa rhizome extract against Cutibacterium acnes.…”
Section: Synergistic Effect Of Lab Antimicrobials With Other Compoundsmentioning
confidence: 99%
“…C. acnes is mainly found in the areas of the skin rich in sebaceous glands; it accounts for about 90% of the total skin microbiota making it the most abundant bacterium 1 , 2 . Its involvement in several disorders like eye infections, prostate cancer, acne vulgaris 3 sarcoidosis 4 and rarely bacterial endocarditis 5 has caused its status shifted from commensal bacterium to an opportunistic pathogen 6 . Acne vulgaris is the most abundant skin disorder mainly effecting adolescents.…”
Section: Introductionmentioning
confidence: 99%